2021
DOI: 10.1097/bpo.0000000000001999
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Operative Management of Pediatric Supracondylar Humerus Fractures: An Analysis of Frequency, Complications, and Cost From 2009 to 2018

Abstract: Background: In an effort to increase the value of health care in the United States, there has been increased focus on shifting certain procedures to an outpatient setting. While pediatric supracondylar humerus fractures (SCHFs) have traditionally been treated in an inpatient setting, recent studies have investigated the safety and efficiency of outpatient surgery for these injuries. This retrospective study aims to examine ongoing trends of outpatient surgical care for SCHFs, examine the safety and complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…In the pediatric population, Makarewich et al demonstrated that the shift to outpatient surgery in type II supracondylar humerus fractures has the potential to reduce cost, with no change in outcomes [ 30 ]. Modest et al subsequently generated similar findings after retrospectively analyzing over 8,000 pediatric patients who underwent operative management of supracondylar humerus fractures [ 29 ]. However, it is difficult to discern whether the association between unplanned re-operation and outpatient procedures is due to differences in case selection, patient co-morbidities, or other factors.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the pediatric population, Makarewich et al demonstrated that the shift to outpatient surgery in type II supracondylar humerus fractures has the potential to reduce cost, with no change in outcomes [ 30 ]. Modest et al subsequently generated similar findings after retrospectively analyzing over 8,000 pediatric patients who underwent operative management of supracondylar humerus fractures [ 29 ]. However, it is difficult to discern whether the association between unplanned re-operation and outpatient procedures is due to differences in case selection, patient co-morbidities, or other factors.…”
Section: Discussionmentioning
confidence: 91%
“…Further research may investigate the causes of unplanned re-operation in emergent/urgent procedures. Regarding the inpatient vs. outpatient setting, there has been a recent trend toward outpatient surgery in many orthopedic subspecialties [ 27 - 29 ]. In the pediatric population, Makarewich et al demonstrated that the shift to outpatient surgery in type II supracondylar humerus fractures has the potential to reduce cost, with no change in outcomes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing trend to treat pediatric SCH fractures in an ambulatory setting [84][85][86] . It has been shown to be not only cost-effective, but also safe, with very low rates of postoperative infections and complications [84][85][86] .…”
Section: Discussionmentioning
confidence: 99%
“…Outpatients had fewer return visits to the emergency department within 1 month. 19 However, outpatient care requires a caregiver at home, the absence of serious medical problems, and reasonable proximity to a surgical center. Although these are not modifiable factors, knowing these resource requirements can prompt surgeons to enlist the help of ancillary support as necessary to optimize value (eg, care coordination for transportation).…”
Section: Timing Of Surgerymentioning
confidence: 99%